Methods for the Separation of Platelets from Plasma - Hutton, R. A; Howard, Margaret A; Deykin, Daniel; Hardisty, R. M (Thrombosis and Haemostasis, 1974)
Platelets have been separated from plasma of a series of normal volunteers by three methods: albumin density-gradient centrifugation, gel filtration, and a combination of the two. The efficacy of these three methods has been assessed by determination of the percentage recovery of the platelets, their aggregability by ADP, collagen and thrombin, platelet factor-3 availability, content and release of platelet adenine nucleotides and electron microscopic appearances. Platelets prepared by all three methods showed some loss of sensitivity to aggregating agents, minor activation of platelet factor 3 and morphological changes, as compared with platelets in PRP. Function and morphology were best preserved in platelets prepared by the combined method and most disturbed in those prepared by repeated washing on an albnmin density gradient.